Feasibility of coupled empirical and dynamic modeling to assess climate change and air pollution impacts on temperate forest vegetation of the eastern United States. (March 2018) - McDonnell, T.C.; Reinds, G.J.; Sullivan, T.J.; Clark, C.M.; Bonten, L.T.C.; Mol-Dijkstra, J.P.; Wamelink, G.W.W.; Dovciak, M.
Abstract: Changes in climate and atmospheric nitrogen (N) deposition caused pronounced changes in soil conditions and habitat suitability for many plant species over the latter half of the previous century. Such changes are expected to continue in the future with anticipated further changing air temperature and precipitation that will likely influence the effects of N deposition. To investigate the potential long-term impacts of atmospheric N deposition on hardwood forest ecosystems in the eastern United States in the context of climate change, application of the coupled biogeochemical and vegetation community model VSD+PROPS was explored at three sites in New Hampshire, Virginia, and Tennessee. This represents the first application of VSD+PROPS to forest ecosystems in the United States. Climate change and elevated (above mid-19th century) N deposition were simulated to be important factors for determining habitat suitability. Although simulation results suggested that the suitability of these forests to support the continued presence of their characteristic understory plant species might decline by the year 2100, low data availability for building vegetation response models with PROPS resulted in uncertain results at the extremes of simulated N deposition. Future PROPS model development in the United States should focus on inclusion of additional foundational data or alternate candidate predictor variables to reduce these uncertainties. Graphical abstract: Highlights: Changes in climate and N deposition are important factors affecting biodiversity. We assess past and future impacts on plant diversity with a soil-plant model chain. Species occurrence probability was mostly driven by changes in N deposition. Further development of statistical plant response functions is needed. Abstract : Climate change and elevated N deposition were simulated to be important factors for determining habitat suitability for plants, and are expected to interact with changes in soil chemistry.